YARIŞ ATLARINDA YUMUŞAK DAMAĞIN DORSALE DEPLASMANININ İNSİDANSININ ARAŞTIRILMASI - SEVİM, MUSTAFA (Fırat Üniveristesi, 2022)
Bu çalışmada safkan arap ve ingiliz yarış atlarında görülen yumuşak damağın dorsale deplasmanının insidansının araştırılması amaçlandı. Çalışmanın materyalini Elazığ hipodromuna getirilen safkan 400 at oluşturdu. İdman ve yarış sonrası muayeneye getirilen atlar travaya alındı. Dudak veya kulağa yavaşa takılarak hayvanlar zapt-ı rap altına alınarak, endoskopik muayeneye hazır hale getirildi. Endoskopik muayenede aparat nasal ventralden girilerek hava keseleri, epiglottis, larinx kıkırdakları ve yumuşak damak muayeneleri yapıldı. Muayene esnasında hayvana yutkunma refleksleri yaptırılarak, yumuşak damağın epiglottis üzerinden ayrılıp ayrılmamasına bakıldı. Atlarda yumuşak damağın dorsale deplasmanı (YDDD) hastalığının cinsiyete göre görülme sıklığı erkeklerde %32.8, dişilerde %25.0 olarak belirlendi. Hastalığın ortaya çıkmasında cinsiyete göre bir farklılık tespit edilmedi YDDD hastalığının ırklara göre görülme sıklığı arap atlarında %30.6, ingiliz atlarında %28.5 olarak belirlendi. Hastalığın ırklara bağlı görülme sıklığının ırklararası istatistiki bir farklılık belirlenmedi. Atlarda YDDD hastalığının yaşa göre görülme sıklığı yaş artıkça %3.6 oranından %76.2 oranına doğru lineer bir artış göstermektedir. Hayvanların yaşa bağlı olarak görülme sıklığını yaş ilerledikçe arttığı tespit edildi. Sonuç olarak; 400 adet atta yapılan araştırmada hastalığın görülme insidansının %29,5 olduğu ve yaş ilerledikçe görülme sıklığının arttığı görüldü.

In this study was aimed to investigate the incidence of dorsal displacement of the soft palate seen in thoroughbred Arabian and English racehorses. The material of the study consisted of 400 purebred horses brought to the Elazig hippodrome. The horses, which were brought to the examination after training and race, were taken into labor. The animals were restrained by fastening the lip or ear and made ready for endoscopic examination. In the endoscopic examination, the air sacs, epiglottis, larynx cartilages and soft palate were examined by entering the apparatus through the nasal ventral. During the examination, swallowing reflexes were performed and it was checked whether the soft palate was separated from the epiglottis. The incidence of dorsal displacement of the soft palate (YDDD) disease in horses by gender was determined as 32.8% in males and 25.0% in females. There was no difference in the occurrence of the disease according to gender. The incidence of YDDD according to races was determined as 30.6% in Arabian horses and 28.5% in English horses. There was no statistical difference between the races of the incidence of the disease depending on the races. The incidence of FDDD in horses according to age shows a linear increase from 3.6% to 76.2% with increasing age. It was determined that the incidence of animals depending on age increased with increasing age. As a result; In a study conducted on 400 horses, it was seen that the incidence of the disease was 29.5% and the incidence increased with age.
Investigation of dorsal displacement the soft palate in race horses
Keywords: Veteriner Hekimliği